2009
DOI: 10.1007/s10152-009-0159-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen stable isotopic inventory of the most abundant demersal fish captured by benthic gears in southwestern Iceland (North Atlantic)

Abstract: Stable isotopes ( 13 C and 15 N) were used to examine the origin of organic matter for the most representative demersal species of the SW Icelandic Wshery, accounting for over 70% of landings of those species in the North Atlantic. Samples were collected during a 2-week period in early September 2004 from landings and directly during Wshing cruises. Stable isotopes showed that particulate organic matter and sedimentary organic matter were at the base of the food web and appeared to Wll two diVerent compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Although sand eel populations were facing a rapid decline, they made up to 70% of the diet across all seasons. Sand eel is a planktivorous primary consumer with a low enrichment of δ 13 C (Sarà et al, 2010). The within species variation of harbour seal δ 13 C in this study (-16.36 ± 2.02 ‰) suggests sand eel was not making up a majority of their diet.…”
Section: Marine Mammalsmentioning
confidence: 52%
“…Although sand eel populations were facing a rapid decline, they made up to 70% of the diet across all seasons. Sand eel is a planktivorous primary consumer with a low enrichment of δ 13 C (Sarà et al, 2010). The within species variation of harbour seal δ 13 C in this study (-16.36 ± 2.02 ‰) suggests sand eel was not making up a majority of their diet.…”
Section: Marine Mammalsmentioning
confidence: 52%
“…Stable isotope mixing models are also sensitive to the number of prey included, and it is possible that some potential prey were excluded from the models, especially for the EG and NHB populations where no studies investigating stomach contents have been conducted. We did investigate many other prey stable isotope values for the two populations (including sandlance (Ferguson, unpublished data), Atlantic cod (Gadus morhua) (Thompson et al 1999, Sarà et al 2009), the shrimps H. glacialis and P. multidentata (Rau et al 1989), and Atlantic halibut (Hippoglossus hippoglossus) (Sarà et al 2009)); however, none of these prey had stable isotope values within the range seen for narwhals in the two populations and thus they were excluded from the stable isotope mixing models. Overall the model results are insightful but should be interpreted with caution.…”
Section: Values and The Highest Dmentioning
confidence: 99%
“…However, some teleosts inhabiting Icelandic waters can use similar resources based on previous stomach content (e.g., Jaworski and Ragnarsson 2006) and stable isotope data (Sarà et al 2009). For example, a recent study reported that Atlantic cod, haddock (Melanogrammus aeglefinus), saithe (Pollachius virens), and ling (Molva molva) sampled in the waters surrounding Iceland had similar d 13 C values (Sarà et al 2009). Hg could be useful for more clearly characterizing the feeding behavior of Greenland sharks and their potential teleost prey in Icelandic waters.…”
Section: Introductionmentioning
confidence: 99%